2014 IFIP Networking Conference 2014
DOI: 10.1109/ifipnetworking.2014.6857103
|View full text |Cite
|
Sign up to set email alerts
|

A first look at 802.11ac in action: Energy efficiency and interference characterization

Abstract: This paper is first of its kind in presenting a detailed characterization of IEEE 802.11ac using real experiments. 802.11ac is the latest WLAN standard that is rapidly being adapted due to its potential to deliver very high throughput. The throughput increase in 802.11ac can be attributed to three factors -larger channel width (80/160 MHz), support for denser modulation (256 QAM) and increased number of spatial streams for MIMO. We provide an experiment evaluation of these factors and their impact using a 18-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 14 publications
1
35
0
Order By: Relevance
“…But these improvements are very sensitive to the channel conditions with the achieved data rates rapidly declining as the distance between the transmitter and the receiver increases. Y. Zeng et al [5] present an early performance characterization of IEEE 802.11ac standard, analyzing the impact of utilizing wider channel widths on energy efficiency and interference, that are basically the main basis for IEEE 802.11ac. The authors show that 80 MHz channel width yields substantial throughput improvement, but the improvements come at the cost of higher power consumption.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…But these improvements are very sensitive to the channel conditions with the achieved data rates rapidly declining as the distance between the transmitter and the receiver increases. Y. Zeng et al [5] present an early performance characterization of IEEE 802.11ac standard, analyzing the impact of utilizing wider channel widths on energy efficiency and interference, that are basically the main basis for IEEE 802.11ac. The authors show that 80 MHz channel width yields substantial throughput improvement, but the improvements come at the cost of higher power consumption.…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…However, they cannot be used for data processing operation. The authors of [12] presented a performance characterization of 802.11ac in a testbed, and they showed that wider bandwidth improves throughput performance at the cost of higher power consumption.…”
Section: Related Workmentioning
confidence: 99%
“…The paper concludes that using legacy RTS/CTS handshake mechanism has some shortcomings that need to be addressed to cope with the new 802.11ac features. In [11], a performance analysis of energy efficiency and interference in 802.11ac is presented. The authors proclaim that more energy is consumed when utilizing wider channel bandwidths, whereas the addition of more spatial streams is energy efficient.…”
Section: Background and Related Workmentioning
confidence: 99%